Effect of Nusinersen on Respiratory and Bulbar Function in Children with Spinal Muscular Atrophy: Real-World Experience from a Single Center - Gaboli, Mirella; López Lobato, Mercedes; Valverde Fernández, Justo; Ferrand Ferri, Patricia; Rubio Pérez, Eloisa; Andrade Ruiz, Henry A.; López-Puerta González, José María; Madruga-Garrido, Marcos (Neuropediatrics, 2024)
Background Due to the limited data from clinical trials and real-world settings in the realm of nusinersen, there is a need for further evidence. This study seeks to assess the impact of nusinersen, when combined with standard care, on bulbar function, respiratory function, and the necessity for respiratory support among pediatric patients with spinal muscular atrophy (SMA).Methods Prospective observational study, involving pediatric SMA patients (Types 1–3) undergoing nusinersen treatment at the Hospital Universitario Virgen del Rocío in Spain over at least 24 months. The cohort included 11 SMA type 1 patients, comprising 6 type 1b and 5 type 1c, 12 SMA type 2 patients, and 5 SMA type 3 patients.Results Twenty-eight pediatric patients were enrolled with the majority being male (n = 20). Patients with type 1 were diagnosed and received treatment significantly earlier than those with types 2 and 3 (p < 0.001). Additionally, there was a longer period between diagnosis and the start of treatment in types 2 and 3 (p = 0.002). Follow-up revealed statistically improved functional and respiratory outcomes associated with earlier initiation of nusinersen treatment at 6, 12, and 24 months in all phenotypes. The ability to swallow and feed correctly remained unchanged throughout the study, with SMA type 1c patients maintaining oral feeding in contrast to patients with SMA type 1b. Notably, no deaths were recorded.Conclusions This study provides important insights into the real-world clinical progress of pediatric SMA patients and their response to nusinersen treatment, highlighting the significance of early intervention for better functional and respiratory outcomes.
Keywords: spinal muscular atrophy; children; nusinersen; respiratory function; bulbar function